2013
DOI: 10.1136/medethics-2013-101424
|View full text |Cite
|
Sign up to set email alerts
|

Togolese lay people's and health professionals’ views about the acceptability of physician-assisted suicide

Abstract: Aim:To study the views of lay people and health professionals in an African country, Togo, of the acceptability of physician-assisted-suicide (PAS). February-June 2012, 322 lay people and 198 health professionals (75 physicians, 60 nurses, and 63 health counselors) in Togo judged the acceptability of PAS in 36 concrete scenarios composed of all combinations of four factors: (a) the patient's age, (b) the level of incurability of the illness, (c) the type of suffering, and (d) the patient's request for PAS. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
6
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 12 publications
2
6
0
1
Order By: Relevance
“…These findings were consistent with previous empirical studies in sub-Saharan African countries that suggested that respect for individual autonomy in health care is not a strongly endorsed value among African people (Kpanake, Dassa, Sorum, & Mullet, 2014;Solum, Maluwa, & Severinsson, 2012; see also Kpanake, 2018). The salience of individual autonomy and self-determination in Western Europe cultural context may explain the French sensitivity to patients' autonomy in health communication.…”
Section: Discussionsupporting
confidence: 90%
“…These findings were consistent with previous empirical studies in sub-Saharan African countries that suggested that respect for individual autonomy in health care is not a strongly endorsed value among African people (Kpanake, Dassa, Sorum, & Mullet, 2014;Solum, Maluwa, & Severinsson, 2012; see also Kpanake, 2018). The salience of individual autonomy and self-determination in Western Europe cultural context may explain the French sensitivity to patients' autonomy in health communication.…”
Section: Discussionsupporting
confidence: 90%
“…In contrast, such a position was held by less than 2% of the African participants. These findings are consistent with previous empirical studies in sub-Saharan African countries that suggested that respect for individual autonomy in health care is not a strongly endorsed value among African people (Kpanake, Dassa, Sorum, & Mullet, 2014;Solum, Maluwa, & Severinsson, 2012). Thus, while in the West any reluctance to tell bad news directly to patients is often blamed on physician paternalism (Beauchamp & Childress, 2008;Jennings, 2014), in Africa it is more a result of people's widely-shared cultural beliefs (Harris, Shao, & Sugarman, 2003;Solum, Maluwa, & Severinsson, 2012).…”
supporting
confidence: 81%
“…Each person was tested individually according to the procedure used in previous studies. 8 The experimenter explained to the participants what was expected, that is, that for each scenario they were to indicate the degree of acceptability of a decision to resort to physician-assisted suicide. They made ratings at their own pace, and the experimenter made certain that the participants understood all relevant information before they made ratings.…”
Section: Methodsmentioning
confidence: 99%